Reliability & life testing handbook. Volume 1 - Kececioglu, Dimitri (DEStech Publications, 2002)
Each volume is a complete guide and reference to product reliability testing. Encyclopedic in scope, it covers all steps from planning and test selection to test procedure and results analysis. Volume 1 delivers must-have information on a variety of distributions, including the Chi-Square, Exponential, Normal, Lognormal, Weibull, Gamma, and others.